Internet resources for neurologists - Al-Shahi, Rustam; Sandercock, P A G (BMJ publishing group, 2003)
This fourth and final review in the JNNPinternet series summarises the essential internet resources for adult and paediatric clinical neurology, neuroradiology, and neurophysiology. This article is freely available on the JNNPwebsite (www.jnnp.com), where—within seconds—the complete list of recommended websites can be easily downloaded and incorporated into your web browser as a Bookmark/Favorite file. The further progress of clinical neurology on the world wide web will be monitored in JNNPNeuronline fillers and JNNP Neurology in Practice supplements.
Keywords: internet resources; neurology